Refugee women's employment in Turkey's humanitarian response to the Syrian crisis :|a qualitative documentary analysis - Gürbüz, Şeyma Nazlı. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Eight years ago, first flow of refugees started to cross the Turkish-Syrian border, fleeing a bloody civil war that started to tear their lives apart while looking for a fresh new start in a new country. Soon after, these refugee flows turned into a humanitarian crisis that no longer seeks emergency actions for its problems but instead necessitates permanent integration strategies that would ease life for both Turkish and Syrian societies. This thesis examines how and to what extent humanitarian actors approach the labor market integration of the Syrian refugee women in Turkey. The thesis relies on exploratory qualitative analysis of documents produced by five prominent humanitarian actors, namely Yuva Association, Support to Life Association, Turkish Red Crescent, Association for Solidarity with Asylum Seekers and Migrants, and United Nations agencies in the post-2016 period, which was the year that the work permits for the Syrians under the temporary protection was issued. The thesis argues that the selected humanitarian actors adopt an approach that fits in between the Basic Needs Approach and the Instrumentalist Approach according to Olivius’ categorization of humanitarian responses to refugee women. The thesis finds that, although the humanitarian actors in Turkey acknowledges the importance of gender mainstreaming in their rhetoric, this acknowledgement is not reflected in their discourse on livelihood programs. Refugee women mostly appears in the humanitarian actor discourses on basic needs programs.
Keywords: Women refugees -- Syria.; Women refugees -- Turkey -- Social conditions.